Soil salinity increases survival of freezing in the enchytraeid Enchytraeus albidus - Silva, A. L. P. (2013)
Enchytraeus albidus is a freeze-tolerant enchytraeid found in diverse habitats, ranging from supralittoral to terrestrial and spanning temperate to arctic regions. Its freeze tolerance is well known but the effect of salinity in this strategy is still poorly understood. We therefore studied the combined effect of salinity (0, 15, 35, 50‰ NaCl) and sub-zero temperatures (-5, -14, -20°C) on the freeze tolerance of E. albidus collected from two distinct geographical regions (Greenland and Germany). A full factorial design was used to study survival, and physiological and biochemical end points. The effect of salinity on the reproduction of German E. albidus was also assessed. Exposure for 48 h to saline soils prior to cold exposure triggered an increase in osmolality and decrease in water content. Worms exposed to saline soils had an improved survival of freezing compared to worms frozen in non-saline soils, particularly at -20°C (survival more than doubled). Differential scanning calorimetry measurements showed that the fraction of water frozen at -5 and -14°C was lower in worms exposed to 35‰ NaCl than in control worms. The lowering of ice content by exposure to saline soils was probably the main explanation for the better freeze survival in saline-exposed worms. Glucose increased with decreasing temperature, but was lower in saline than in non-saline soils. Thus, glucose accumulation patterns did not explain differences in freeze survival. Overall, the physiological responses to freezing of E. albidus from Greenland and Germany were similar after exposure to saline soils. Soil salinity up to 30‰ improved reproduction by a factor of ca. 10.